Nitric oxide regulates ganoderic acid biosynthesis by the S‐nitrosylation of aconitase under heat stress in Ganoderma lucidum. (24th June 2020) - Liu, Rui; Zhu, Ting; Yang, Tao; Yang, Zhengyan; Ren, Ang; Shi, Liang; Zhu, Jing; Yu, Hanshou; Zhao, Mingwen
Summary: Nitric oxide (NO) is an important signalling molecule in stress response of organisms. We previously reported that NO decreases heat stress (HS)‐induced ganoderic acid (GA) accumulation in Ganoderma lucidum . To explore the mechanisms by which NO modulates GA biosynthesis under HS, the effect of NO on the reactive oxygen species (ROS) content was examined. The results showed that NO decreased the production of mitochondrial ROS (mitROS) by 60% under HS. Further research revealed that NO reduced the mitROS content by inhibiting aconitase (Acon) activity. The GA content in Acon‐silenced (Aconi) strains treated with NO donor did not differ significantly from that in untreated Aconi strains. To study the mechanism by which Acon activity is inhibited, the S‐nitrosylation level of Acon was determined. Biotin‐switch technology and mass spectrometry analysis were used to show that Acon is S‐nitrosylated at the Cys‐594 amino acid residue. Substitution of Cys‐594 with a Ser, which cannot be S‐nitrosylated, abolished the responsiveness of Acon to the NO‐induced reduction in its enzymatic activity. These findings demonstrate that NO inhibits Acon activity through S‐nitrosylation at Cys‐594. In summary, these findings describe mechanism by which NO regulates GA biosynthesis via S‐nitrosylation of Acon under HS condition in G . lucidum .